Comparison of Iris Calved IOL and LASIK Surgery Outcome in Mongolian Patients - Gunchin-Ish, Narangarav; Soningerel, Batochir; Davaatseren, Uranchimeg (Central Asian Journal of Medical Sciences, 2022)
Objective: There are significantly few studies which have introduced the comparison intra ocular lens (IOL) outcome with conventional phacoemulsification surgery. Thus, in the present study, we aimed to compare anterior chamber intra ocular lens (AC IOL) and LASIK surgery in Mongolian patients. Methods: This study was conducted on 67 participants. Females comprised 58.8 % in the IOL patients and 72.0 % in the LASIK groups. The mean age of the participants was 32.06 ± 9.29 in IOL and 29.4 ± 6.59 in the LASIK group. Results: Pre operative uncorrected visual activity (UCVA) was 7.94 ± 6.56 in IOL patients, and 2 weeks after surgery, UCVA had increased to 61.18 ± 21.18. In the case of LASIK, pre-operative UCVA was 20.56 ± 17.20, and the value was 86.8 ± 18.23 after surgery. Pre-operative best-corrected visual acuity (BCVA) IOL and LASIK group were 37.65 ± 18.38 and 97.6 ± 4.31, respectively. However, only IOL patients had significantly improved BCVA after surgery (71.76 ± 22.97 at post-operative 2nd week). Conclusions: The best-corrected visual acuity and was better for AC IOL than LASIK surgery.